Metode Failure Mode and Effect Analysis (FMEA) sebagai penilaian risiko pada perbankan syariah - Aprelia, Nala Widya (Maliki Interdisciplinary Journal, 2025)
This research examines the methods that can be applied in conducting risk assessment in Islamic banking. In optimizing performance, banks need to analyze existing risks so that they can prevent and minimize their impact on banking. One of them is conducting an assessment with the Failure Mode and Effect Analysis (FMEA) method as an identification of problems that occur. The approach chosen in this research is descriptive qualitative with data collection for the last 10 years. This research explains the purpose of applying the FMEA method to analyze risks that will be ranked into priority levels so that companies can take immediate action according to the needs at hand. There are several steps taken when using the FMEA method. With this FMEA method, it will have an impact on risk management in Islamic banking and can help directors to make decisions in formulating policies that strengthen and optimize Islamic banking business operations.